The Effect of Toxicity, Physical and Thermal Properties of Fire Blanket Made of Glass Fiber on Its Quality as Small Fire Suppression Tool - Mohamed A. Hassan; Mohamed M. AlSofian; Ahmed Al Zharani; Mohammed R. AlOtaibi; Sami Al Saeed; Naif Al Anazi (Fire)
The use of fiberglass blankets as fire suppression blankets to extinguish accidental cooking fires has been regulated and widely used, especially in homes and small firms and laboratories. Understanding the properties, which have significant effect on their performance, is essential for ensuring effective fire control and improving the quality of these blankets in fire suppression. This study examines key properties including toxicity, physical characteristics, thermal behavior, and fire suppression capabilities. Novel properties such as air permeability and spectroscopic structural analysis are explored, areas previously under-researched. The sample number S4 had Warp/weft count 21/12 with comparison to air permeability; it gave the lowest value among the selected samples. Thermal properties, including heat transfer and temperature dynamics, are also analyzed to understand how fire spreads through the material. The optimal performance of air permeability was observed to be below 650 L/m2/s. Blankets demonstrated over 45% heat blocking efficiency at low heat flux and more than 78% at high heat flux. Temperature rise within the first minute of fire exposure is a key determinant, with effective blankets maintaining temperatures below 300 °C after one minute and ensuring that the final temperature after three minutes does not exceed 390–400 °C. Additionally, a new classification system based on the toxicity of gases emitted during combustion was introduced, enhancing the safety profile of fiberglass blankets and improving their suitability for practical use. This research contributes valuable insights into both the performance and safety of fiberglass fire blankets